The neural crest stem cells: control of neural crest cell fate and plasticity by endothelin-3 - Elisabeth Dupin (Anais da Academia Brasileira de Ciências, 2001)
How the considerable diversity of neural crest (NC)-derived cell types arises in the vertebrate embryo haslong been a key question in developmental biology. The pluripotency and plasticity of differentiation of theNC cell population has been fully documented and it is well-established that environmental cues play animportant role in patterning the NC derivatives throughout the body. Over the past decade, in vivo and invitro cellular approaches have unravelled the differentiation potentialities of single NC cells and led to thediscovery of NC stem cells. Although it is clear that the final fate of individual cells is in agreement with theirfinal position within the embryo, it has to be stressed that the NC cells that reach target sites are pluripotentand further restrictions occur only late in development. It is therefore a heterogenous collection of cells thatis submitted to local environmental signals in the various NC-derived structures. Several factors were thusidentified which favor the development of subsets of NC-derived cells in vitro. Moreover, the strategy ofgene targeting in mouse has led at identifying new molecules able to control one or several aspects of NC celldifferentiation in vivo. Endothelin peptides (and endothelin receptors) are among those. The conjunction ofrecent data obtained in mouse and avian embryos and reviewed here contributes to a better understanding ofthe action of the endothelin signaling pathway in the emergence and stability of NC-derived cell phenotypes.